2013
DOI: 10.1155/2013/196493
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Diagnostic Biopsy for Cutaneous Melanoma: Implications for Surgical Oncologists

Abstract: Background and Objectives. While excisional biopsy is recommended to diagnose cutaneous melanoma, various biopsy techniques are used in practice. We undertook this study to identify how frequently final tumor stage and treatment recommendations changed from diagnostic biopsy to final histopathology after wide local excision (WLE). Methods. We compared the histopathology of the dermatopathologist-reviewed diagnostic biopsy and final WLE in 332 cutaneous melanoma patients. Results. Tumor sites were extremity (51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 21 publications
1
44
0
Order By: Relevance
“…Whereas multiple studies have reported that primary melanoma mitoses predict SLN status [12,13,19], others have reported no such association, with up to one-third of SLN-positive T1 melanomas having zero mitoses [15,16,20]. A positive deep biopsy margin may be associated with a higher likelihood of nodal metastasis for T1 melanoma patients with no otherwise discernible indication for SLNB (8.3% in one series), but it was recently dropped from National Comprehensive Cancer Network guidelines as an indication for consideration of SLNB [21,22]. Ulceration, which continues to classify thin melanomas as T1b, also has been reported as a factor that is variably associated with nodal status, but is a rare finding (1-15%) in thin melanomas [16].…”
Section: Discussionmentioning
confidence: 98%
“…Whereas multiple studies have reported that primary melanoma mitoses predict SLN status [12,13,19], others have reported no such association, with up to one-third of SLN-positive T1 melanomas having zero mitoses [15,16,20]. A positive deep biopsy margin may be associated with a higher likelihood of nodal metastasis for T1 melanoma patients with no otherwise discernible indication for SLNB (8.3% in one series), but it was recently dropped from National Comprehensive Cancer Network guidelines as an indication for consideration of SLNB [21,22]. Ulceration, which continues to classify thin melanomas as T1b, also has been reported as a factor that is variably associated with nodal status, but is a rare finding (1-15%) in thin melanomas [16].…”
Section: Discussionmentioning
confidence: 98%
“…Bolshinky and colleagues showed following apparently complete excisional biopsy, 3.6% of WLEs had residual melanoma with a third of these cases requiring a second (three‐stage) or third (four‐stage) excision . Other studies have found similar, 2% rates of additional surgery following excisional biopsy and 2–5% rates of additional surgery following shave biopsy …”
Section: Introductionmentioning
confidence: 88%
“…Melanoma base transection is common in shave biopsies, the incidence ranging from 9% to 68% . Breslow tumour thickness (vertical depth of invasion) is the single most important prognostic characteristic of the primary tumour; it guides determination of the definitive resection margins and informs decisions about the appropriateness of sentinel lymph node biopsy (SLNB).…”
Section: Why Base Transection Mattersmentioning
confidence: 99%